Authority for Calculating State Economic Losses in Criminal Acts of Corruption in Indonesia - Hartati; Hafrida; Erwin; Arizyanto, Romi; Beny Saputra (Jurnal IUS Kajian Hukum dan Keadilan, 2024)
This article will analyze the elements and authority to calculate state economic losses to achieve justice for criminal acts of corruption in Indonesia. The research methodology employed is normative juridical, with a focus on literature reviews and relevant legislation. The research findings indicate that corruption is not only related to state financial losses but also to state economic losses. The regulation of elements of state economic losses and the authority to calculate state economic losses in Indonesia have not been regulated firmly and completely in laws and regulations so it will give rise to different interpretations from law enforcement officers. The unclear regulation of elements and authority in calculating state economic losses will result in different indicators for determining the value of calculating state economic losses which will result in different results of calculating state economic losses which can be detrimental the defendant because the calculation results exceed the unlawful acts he committed and can also detrimental the state if the calculation results are much lower than the state economic losses incurred.